2005
DOI: 10.1016/j.nima.2004.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Study of the radiation hardness of CsI(Tl) scintillation crystals

Abstract: This paper is devoted to the study of a degradation of CsI(Tl) crystals scintillation characteristics under irradiation with γ-quanta at the uniformly distributed absorbed dose up to 3700 rad. The sample set consisted of 25 crystals of 30 cm long having a truncated pyramid shape and 30 rectangular crystals of the same length. A large difference in the light output deterioration caused by the radiation was observed for the samples of the same shape. A substantial dependence of the average light output loss from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 13 publications
3
14
0
Order By: Relevance
“…The light yield relative to 0 Gy dose for all crystals at all irradiation stages is shown in Figure 3. For the spare Belle crystals, our measurements agree with a previous study of uniformly irradiated Belle CsI(Tl) crystals up to 37 Gy [8] and extend these results up to 1000 Gy showing that the light yield degradation continues to plateau requiring an order of magnitude more dose to have the same relative drop in light yield. This plateauing light output loss trend is observed for both BABAR and Belle crystals.…”
Section: Light Yield Degradationsupporting
confidence: 89%
See 3 more Smart Citations
“…The light yield relative to 0 Gy dose for all crystals at all irradiation stages is shown in Figure 3. For the spare Belle crystals, our measurements agree with a previous study of uniformly irradiated Belle CsI(Tl) crystals up to 37 Gy [8] and extend these results up to 1000 Gy showing that the light yield degradation continues to plateau requiring an order of magnitude more dose to have the same relative drop in light yield. This plateauing light output loss trend is observed for both BABAR and Belle crystals.…”
Section: Light Yield Degradationsupporting
confidence: 89%
“…As the path length of scintillation photons is much longer in large sized crystals used in collider experiments, increased self-absorption is expected to have a more significant effect on the degradation of the detected light yield in these crystals. This was suggested in a past study where a small sample crystal dosed to 500 Gy showed negligible light output loss compared to several 30 cm long crystals dosed to 37 Gy [8].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Calorimeters made of CsI scintillators, which achieve the best energy resolution for photons and electrons, as well as high energy physics experiments (e.g. synchrotron-based protein crystallography (PX)) and non-destructive evaluation, are based on the fact that the radiation hardness of CsI are retained at acceptable levels after the absorption of radiation doses up to a few hundred rads (Beylin et al, 2005;Labanti et al, 2008;Tsuji et al, 2010;Kocak et al, 2011;Woo and Kim, 2012). The most important feature of CsI:Tl scintillators is their ability to grow in columnar structure (Kim et al, 2007).…”
Section: Introductionmentioning
confidence: 99%